2018
DOI: 10.1007/s00424-018-2227-8
|View full text |Cite
|
Sign up to set email alerts
|

Endurance exercise protects skeletal muscle against both doxorubicin-induced and inactivity-induced muscle wasting

Abstract: Repeated bouts of endurance exercise promotes numerous biochemical adaptations in skeletal muscle fibers resulting in a muscle phenotype that is protected against a variety of homeostatic challenges; these exercise-induced changes in muscle phenotype are often referred to as "exercise preconditioning". Importantly, exercise preconditioning provides protection against several threats to skeletal muscle health including cancer chemotherapy (e.g., doxorubicin) and prolonged muscle inactivity. This review summariz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 112 publications
(162 reference statements)
0
21
0
Order By: Relevance
“…Except for pharmacological treatments, emerging evidence suggests that exercise might ameliorate the detrimental effects of doxorubicin on skeletal muscle tissue. A recent review of Powers et al (2019), including preclinical studies, suggests that endurance exercise training performed prior to doxorubicin treatment protects against doxorubicin‐induced skeletal muscle atrophy by the prevention of excess oxidative stress and the activation of proteolytic signalling pathways . Indeed, the beneficial effects of exercise are confirmed in human studies with several clinical trials showing that combined resistance and endurance training has positive effects on muscle strength in cancer patients undergoing chemotherapy .…”
Section: Discussionmentioning
confidence: 99%
“…Except for pharmacological treatments, emerging evidence suggests that exercise might ameliorate the detrimental effects of doxorubicin on skeletal muscle tissue. A recent review of Powers et al (2019), including preclinical studies, suggests that endurance exercise training performed prior to doxorubicin treatment protects against doxorubicin‐induced skeletal muscle atrophy by the prevention of excess oxidative stress and the activation of proteolytic signalling pathways . Indeed, the beneficial effects of exercise are confirmed in human studies with several clinical trials showing that combined resistance and endurance training has positive effects on muscle strength in cancer patients undergoing chemotherapy .…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, skeletal muscle responds to periods of muscle inactivity by initiating processes that facilitate muscle atrophy. Inactivity-induced muscle atrophy occurs as a result of conditions that significantly decrease the work performed by skeletal muscle such as limb-immobilization, prolonged bedrest, and mechanical ventilation-induced inactivity of inspiratory muscles [12,[82][83][84][85][86][87]. Unfortunately, prolonged inactivity results in skeletal muscle atrophy that is detrimental due to a reduced forcegenerating capacity of skeletal muscle.…”
Section: Calpains In Inactivity-induced Muscle Atrophymentioning
confidence: 99%
“…Atrogin1 and MuRF1 increased during muscle atrophy, and, as such, it is verified with the use of DOX [ 12 ]. On the other hand, endurance and resistance exercise protects against the disorders in the skeletal muscle resulted from the use of doxorubicin therapy [ 11 , 13 , 26 ]. In this study, we demonstrated that DOX upregulates the expression of these proteins and that EXER performed during and after chemotherapy minimizes muscle atrophy caused by this pharmacological treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity is associated with a lower prevalence of various types of cancer, including colon, endometrial, breast, prostate, gastroesophageal, ovarian, pancreatic and lung cancers [ 9 ]. In fact, endurance exercise (EXER) offers an approach to managing muscle atrophy and reduces tumor growth [ 10 , 11 ]. Moreover, studies have suggested that in the absence of a tumor, physical exercise is able to protect the muscle during DOX treatment [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%